THE EFFECT OF COUNTRY OF ORIGIN AND CELEBRITY ENDORSEMENT ON PURCHASE DECISIONS VIVO SMARTPHONE PRODUCTS (Case Study on Cellular Global Customers in Tebing Tinggi City) - Irada Sinta; Rico Nur Ilham; Muhammad Multazam; Rista Sihombing; Suci Puji Suryani (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
In this study the population was Tebing Tinggi City Cellular Global Customers, namely as many as 50 people through pre-survey data from researchers to research objects. Because the target population is less than 100, the sampling technique used is the census method, where the entire population of Global Cellular Customers in Tebing Tinggi City is 50 people. Research resultthe first hypothesis is accepted, meaning that Country Of Origin (X1) has a significant effect on Purchase Decision (Y). the second hypothesis is rejected, meaning that Celebrity Endorsement (X2) has no significant effect on Purchase Decision (Y). the third hypothesis is accepted, meaning that the Country Of Origin Variable (X1), Celebrity Endorsement Variable (X2), has a significant simultaneous effect on the Purchasing Decision Variable (Y).